MIKROORGANISME LOKAL DALAM PENGOMPOSAN PADA MUTULOBAK VAR. GREENBOW YANG DIPANEN BERBEDA - Linlin Parlinah; Odang Hidayat (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2016)
The use of local microorganisms in the composting process will influence the final outcome compost or different according to the dominant species of microorganisms contained in the local microorganisms. This indirectly will respond differently to the growth and quality of radish tubers produced. Formulation of the problem of the research is as follows: How is the interaction between the use types of microorganisms locally in the process of composting organic material and harvesting time in the cultivation of rapeseed for the quality of radish, what type of microorganisms local and harvest time how many days after planting gives the crop rapeseed best. The research was conducted in the greenhouse of the Faculty of Agriculture, Winaya Mukti University. Experimental approach using experimental design factorial randomized block design consists of the first factor of compost a wide treatment with different local microorganisms, consists of five levels, and the second factor of different harvesting time which consists of four levels that are repeated twice. The results showed local Microorganisms snails on composting give significantly different results on the length and weight of tuber tubers radish Var. Greenbow, while the quality of radish tubers obtained from harvesting time at the age of 53 HST.